Photosynthetic and evolutionary determinants of the response of selected C3 and C4 (NADP-ME) grasses to fire - Martin, Tarryn (Rhodes University, Faculty of Science, Botany Department, 2009)
Species possess characteristics that are considered adapted to burning and these allow them to outcompete species and dominate in fire prone environments. It has therefore been proposed that fire might have played a critical role in the observed expansion of the grasslands, during the late Miocene. The aim of this study was (i) to investigate whether plant response to fire was a result of physiology or (ii) whether it was due to phylogenetic history. This was achieved by doing a pair-wise comparison between Panicoideae (and Panicoideae) and non-Panicoideae (Danthonioideae and Aristidoideae) species. Pre-fire characteristics, that would enhance fire frequency and assist with plant recovery after burning, were compared across phylogenies and photosynthetic type. Post fire plant recovery was then followed in a field and pot comparison which examined the re-growth of the leaf canopy area, leaf mass, above-ground biomass and the cost of this to the below-ground biomass. The pre-fire characteristics showed both a photosynthetic and phylogenetic response. It was found that the species showed a greater canopy death during winter and had a lower moisture content than the species. These characteristics would potentially contribute towards a larger fuel load in the species. However, the comparison of the dead standing biomass at the end of winter and the below-ground biomass, showed a phylogenetic response with the Panicoideae having a proportionally larger dead standing biomass and below-ground biomass than the non-Panicoideae. These results suggest that not only did the Panicoideae have a larger potential fuel load but that they also shunted carbon below-ground, enabling a fast recovery after being burned. The post-fire results were more strongly determined by phylogeny than by photosynthetic type. The Panicoideae recovered faster and more completely than the non-Panicoideae grasses, possibly contributing to their success and expansion under conditions of increased fire frequency. Although recovery of the and Panicoideae were similar, frequently burnt grasslands are dominated by the Panicoideae. Hence, this dominance cannot be explained by differences in their fire responses and may be determined by the post-fire environmental conditions that potentially advantage species possessing the photosynthetic pathway. Panicoideae dominance is limited to mesic environments where fire is the likely driver of grassland expansion while more arid environments are dominated by non-Panicoideae species. Representative species from these non-Panicoid subfamilies showed poor recovery after fire. This suggests that factors other than fire were the likely drivers of these xeric grassland expansions. The ability of these subfamilies, and particularly the species, to cope with drought remains a likely selective mechanism that requires further research.
Keywords: Photosynthesis; Carbon -- Metabolism; Grasses -- Adaptation; Plants -- Effect of fires on; Grasses -- Research; Grasses -- Physiology; Grasses -- Evolution; Grasslands -- Research